Hepatitis C virus risk factors in the Turkish community - (:unkn) unknown (SPRINGER, 2005)
Hepatitis C virus (HCV) is the most common chronic blood-borne infection in the worldwide. This infection is often insidious and one-half of infected patients are asymptomatic. Determination of risk factors for HCV transmission is very important. The aim of this study was to assess the risk factors, transmission to spouses and children for HCV infection in Turkish population. One hundred and fifty-one patients with chronic hepatitis C and 151 control cases were investigated for the probable risk factors of HCV infection. Complete blood count, ALT, AST, albumin, prothrombin time, upper abdomen ultrasonography assessment and percutaneous liver biopsy (not for cirrhotics) were performed in all patients with chronic hepatitis C. Anti-HCV testing was done by using second-generation ELISA in 302 cases. Minor surgical operation (p < 0.001), major surgical operation (p = 0.001), blood transfusion (p < 0.001), multi-partner sex (p < 0.05), frequent dental therapy (p < 0.05), and dental extraction (p < 0.001) in patients with a chronic HCV infection were found to be higher than the control group. No significant difference was found in other risk factors. The rate of hepatitis C virus in index cases was found to be 1.8% in their spouses and 1.2% in their children. Our study showed that surgical operation, frequent dental therapy, dental extraction, multi-partner sex, and blood transmission are the main risk factors for HCV infection in Turkish community.
Keywords: hepatitis C virus; risk factor; transmission; Turkish community; SEXUAL TRANSMISSION; BLOOD-DONORS; INFECTION; PREVALENCE